Increased mortality for pregnancy‐associated melanoma: systematic review and meta‐analysis. (17th February 2015) - Byrom, L.; Olsen, C.; Knight, L.; Khosrotehrani, K.; Green, A.C.
Abstract Among women, pregnancy‐associated melanomas may have a poorer prognosis than other melanomas, but evidence is inconsistent. We conducted a systematic review and meta‐analysis to assess the effect on melanoma outcome of a coinciding pregnancy. The objective of the study was to conduct a systematic review and meta‐analysis of risk of death from, or recurrence of, pregnancy‐associated melanomas compared with other melanomas in women of reproductive age. Cochrane (1996–2013), MEDLINE (1950–2013), EMBASE (1966–2013), CINAHL (1982–2013), and PUBMED (1951–2013) databases were searched for studies assessing the risk of death and recurrence in pregnancy‐associated melanomas. Eligible studies investigated melanoma outcomes in women with pregnancy‐associated melanomas (diagnosed during pregnancy or in 12 months following pregnancy), included a comparison group and reported measures of risk of melanoma death or disease‐free survival. Eligible study designs were cohort studies of women of childbearing age with confirmed diagnoses of cutaneous melanoma. Individual study effect estimates were pooled using the weighted average method. Studies that did not report a quantitative estimate were summarized narratively. Of 304 citations identified, 14 studies met the inclusion criteria, with assessed outcomes being melanoma death (7), recurrence (3), or both (4). Pooled estimates of mortality risk from four studies showed increased risk of melanoma death after adjustment for patient age and stage of melanoma (pHR 1.56, 95% CI 1.23–1.99) for pregnancy‐associated melanoma compared with other melanomas. Based on limited quantitative evidence, pregnancy‐associated melanomas appear to have poorer outcomes than other melanomas.